Analisis Faktor Yang Mempengaruhi Fluktuasi Nilai Tukar Petani Cabai Merah (Capsicum annum L.) di Jawa Barat - Sa'diyah, Halimatus; Widyastuti, Dyah Erni; Mazwan, M. Zul (Universitas Galuh, 2024)
The farmer exchange rate provides an overview of the welfare of farmers through a comparison of revenues and costs incurred by farmers. The exchange rate of farmers, especially red chili plants is a horticultural commodity that often experiences price fluctuations. Red chili is categorized into the group forming inflation in Indonesia (volatile food). The purpose of this study is to determine the development of the exchange rate of red chili farmers in 2012-2021 and determine the factors that affect the exchange rate of red chili farmers in West Java Province. The research method used is quantitative descriptive analysis. Data collection methods through literature studies and types of data are secondary from the Central Statistics Agency, Pusdatin, and relevant research journals. Data processing using multiple linear regression analysis with the help of Microsoft Excel and SPSS 17.0 applications. The results showed simultaneously and partially that the variables of harvest area, amount of production, fertilizer costs, and producer prices had a significant effect on the exchange rate of red chili farmers in West Java Province. The variable area of harvest and producer price are negative, while the variable amount of production and cost of fertilizer are positive.